Youth nightlife at home: towards a feminist conceptualisation of home. Issue 1 (2nd January 2021) - Pelzelmayer, Katharina; Landolt, Sara; Truong, Jasmine; Labhart, Florian; Santani, Darshan; Kuntsche, Emmanuel; Gatica-Perez, Daniel
ABSTRACT: This paper explores home as a space of youth nightlife and drinking through a feminist lens. It draws on feminist geographical scholarship on home and 40 semi-structured interviews with young people aged 16–25 in Switzerland in the context of a larger interdisciplinary study. We find that the home figures as a central space of nightlife for young people beyond pre-drinking or home parties. At the same time, privacy and intimacy are important to young people when drinking alcohol outside of the home. We suggest that this preference of privacy when going out indicates an interweaving of private and public spheres in young people's nightlives. The paper argues that the home is both a central concrete space and an important symbolic notion in young people's nightlives. In so doing, it empirically complicates the public/private dualism and contributes to feminist geographical conceptualisations of home in the context of youth nightlife.